VD_FINDINFO HC / 2009 / 90 vom 5. Juni 2009 - VD Tribunal cantonal (2009)
RÉPUDIATIONDROIT SUCCESSORAL, RÉVOCATIONEN GÉNÉRAL, ERREUR, ERREUR SUR LES MOTIFS, ERREUR ESSENTIELLE, POUVOIR D'EXAMEN | 566 al. 1 CC, 566 CC, 23 CO, 24 al. 1 ch. 4 CO, 24 al. 2 CO, 24 CO, 489 CPC, 543 CPC